Islamic Education Student Management - Kholis, Nur; Slamet Untung; Muhammad Agus Salim (Jurnal Scientia, 2024)
This research is qualitative research whose data was obtained by conducting library research directed at understanding the messages in a text. The findings of the research results are that student management is a process of managing all matters related to students in a school, starting from planning, accepting students, coaching carried out while students are at school, until students complete their education through creating a learning atmosphere that is conducive and constructive to the ongoing learning process. effective teaching and learning process. Student management aims to organize activities in the student affairs sector so that the learning process carried out in a school can run smoothly, orderly and orderly in such a way that the main objectives of a learning program in a school can be achieved optimally.